Nurse-led coaching of shared decision-making for women with ductal carcinoma in situ in breast care centers: A cluster randomized controlled trial. (May 2019) - Berger-Höger, Birte; Liethmann, Katrin; Mühlhauser, Ingrid; Haastert, Burkhard; Steckelberg, Anke
Abstract: Background: Women with breast cancer demand informed shared decision-making. Guidelines support these claims. Objectives: To investigate whether an informed shared decision-making intervention for women with 'ductal carcinoma in situ' comprising an evidence-based decision aid with nurse-led decision coaching enhances the extent of the mutual shared decision-making behavior of patients and professionals regarding treatment options, and to analyze implementation barriers. Design: Cluster randomized controlled trial with accompanying process evaluation. Setting: Certified breast care centers in Germany. Participants: Women with ductal carcinoma in situ and no previous history of breast cancer facing a primary treatment decision. Methods: Sixteen breast centers were randomized to intervention or standard care to recruit 192 patients (partially-blinded). All coaching sessions and physician consultations were videotaped to assess the primary outcome 'extent of patient involvement in shared decision-making' using the MAPPIN-Odyad observer instrument (scores 0 to 4). Secondary endpoints included the sub-measures of the MAPPIN-inventory (MAPPIN-Onurse, MAPPIN-Ophysician, MAPPIN-Opatient, MAPPIN-Qnurse, MAPPIN-Qpatient and MAPPIN-Qphysician ), 'informed choice', 'decisional conflict' and 'duration of consultations'. Primary intention-to-treat analyses were on cluster level comparing means of cluster values using t-tests. An accompanying process evaluation was conducted comprising 1) analysis of all video recordings with focus on procedures and intervention fidelity and 2) field notes of researchers and feedback from professionals and patients assessed by questionnaires and interviews with focus on barriers and facilitators for implementation at different time points. Results: Due to protracted recruitment, the study was terminated after 14 centers had included 64 patients (intervention group 36, control group 28). Patient participation in informed shared decision-making was significantly higher in the intervention group (mean (SD) score 2.29 (0.56) vs. 0.42 (0.51) in the control group; difference 1.88 (95% CI 1.26–2.50, p < 0.0001). 47.7% women in the intervention group made informed choices, but none in the control group, difference 47.7% (95% CI 12.6–82.7%, p = 0.016). In the intervention group physician consultations lasted 12.8 (6.6) min. vs. 24.3 (6.3) min. in the control group. Physicians' attitudes, false incentives and structural barriers hindered implementation of informed shared decision-making. Nurses appreciated their new roles. Conclusions: Informed shared decision-making is not yet implemented in German breast care centers. Nurse-led decision coaching grounded on evidence-based patient information enhances informed shared decision-making. Trial registration No. ISRCTN46305518.